The Effect of Orientation Degree of Electrospun Polystyrene Fiber on Filtration Performance of Fiber Membrane. Issue 2 (March 2022) - Zheng, Yuansheng; Gao, Jingyuan; Liu, Kai; Ge, Cheng
In this study, ultrafine polystyrene fiber membranes with different fiber orientation degrees were prepared by and electrospinning method, and two methods were used to characterize the fiber orientation degree. In addition, the effects of fiber orientation degree on the surface wettability and smoke filtration performance of fiber membrane were studied. The results showed that the water repellency and smoke absorption capacity of the polystyrene fiber membrane decrease with the increasing fiber orientation degree and the porosity. The orientation degree of the fiber has a significant influence on the smoke filtration performance of fiber membrane.